Rhodococcus globerulus bacteremia in an allogeneic hematopoietic stem cell transplant recipient: report of the first transplant case and review of the literature. Issue 3 (2nd May 2014) - Ramanan, P.; Deziel, P.J.; Razonable, R.R.
Abstract Rhodococcus species are environmental organisms that predominantly cause opportunistic infections in immunocompromised hosts. Rhodococcus equi is the most common species associated with human infections, but there are uncommon but increasing number of cases of infections caused by non‐equi Rhodococcus species. We report a case of Rhodococcus globerulus bacteremia in an allogeneic hematopoietic stem cell transplant recipient, who presented with subacute systemic illness accompanied by severe hepatitis. In the context of this case, we review the literature on Rhodococcus species infections in transplant recipients.